A Reflection on Women Attire in The Quran; A Study On Ayat Al-Hijāb (UINSI Samarinda, 2017)
Hijab, jilbab or khimar known as a piece of garment which usually worn by Muslim women in order to obey their God. It becomes a symbol that shows their identity. Besides, Hijab has a particular meaning according to multiple perspectives which resulted variant styles and types of hijab in one community, with or without syari’ah compliance. Fashion trends also plays the role in modifying women attire and the issue about this seems more complicated since the guidelines were avoided. This paper will goes through the commentaries of Qur’an to examine the requirements of proper women attire as mentioned specifically on ayat al-hijab. It results that Qur’an already put some guidelines on proper attire for Muslim women such as: the garments used to cover body parts is must be long, wide and thick enough. Not being overdressed also included as a requirement.Keyword: Hijab, Women Attire, Syari’ah compliance, Islamic Dress Code.